HARAPAN LANSIA TERHADAP KEGIATAN BINA KELUARGA LANSIA DI DESA SUNGAI SELODANG KECAMATAN SUNGAI MANDAU KABUPATEN SIAK - Bahar, Aswandi; ', Evriyani; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study is based on the condition of the Elderly Family Development program activities in terms of Hope Elderly Against Elderly Family Development activities in Desa Sungai Selodang Kecamatan Sungai Mandau Kabupaten Siak. The research problems are whether Hope Against Elderly Elderly Family Development activities in Desa Sungai Selodang Kecamatan Sungai Mandau Kabupaten Siak performing well?. The purpose of this study was to determine the Elderly Hope Against Elderly Family Development activities in Desa Sungai Selodang Kecamatan Sungai Mandau Kabupaten Siak. The population in this study were 49 and 20 people for the trials, the technique of sampling techniques used are saturated Sampling Simple as many as 49 people. Instrument of data collection is a questionnaire with 173 statements and after the trial live 160 valid statement to be used as a research instrument. Data analysis through quantitative descriptive analysis. From the calculation of the percentage of responses obtained by the research findings Hope Elderly Of Activity Family Development Elderly in Desa Sungai Selodang Kecamatan Sungai Mandau Kabupaten Siak is very high on indicators of control with the average percentage (SS + S) 97.677%, this means that Bina Family Elderly in Rural Selodang river Mandau Siak river District has not done well so Hope Against Elderly Elderly Family Development activities in Desa Sungai Selodang Kecamatan Sungai Mandau Kabupaten Siak is high.Keywords: Hope, Seniors, Elderly Family Development Program.